2021
DOI: 10.3390/ma14030616
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Quantum Dots as Intracellular Imaging-Based Temperature Sensors

Abstract: Non-invasive temperature sensing is necessary to analyze biological processes occurring in the human body, including cellular enzyme activity, protein expression, and ion regulation. To probe temperature-sensitive processes at the nanoscale, novel luminescence nanothermometers are developed based on graphene quantum dots (GQDs) synthesized via top-down (RGQDs) and bottom-up (N-GQDs) approaches from reduced graphene oxide and glucosamine precursors, respectively. Because of their small 3–6 nm size, non-invasive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 49 publications
(94 reference statements)
0
20
0
Order By: Relevance
“…[178] Chemical inertness, appreciable photostability, non-toxicity, hydrophilicity, and high solubility in an aqueous environment make GQDs lucrative for biosensing applications. [35,36] The higher surface area of GQDs maximizes their contact with analyte molecules and also results in a higher electrochemical surface area. This promotes interaction with electroactive species and facilitates direct electron transfer reactions from enzymes and proteins.…”
Section: Electrochemical Characteristics Of Gqdsmentioning
confidence: 99%
“…[178] Chemical inertness, appreciable photostability, non-toxicity, hydrophilicity, and high solubility in an aqueous environment make GQDs lucrative for biosensing applications. [35,36] The higher surface area of GQDs maximizes their contact with analyte molecules and also results in a higher electrochemical surface area. This promotes interaction with electroactive species and facilitates direct electron transfer reactions from enzymes and proteins.…”
Section: Electrochemical Characteristics Of Gqdsmentioning
confidence: 99%
“…For instance, pH sensing in HeLa cells using folic acid-encapsulated GQDs has been reported, where a pH increase from 5–8 results in an increase in emission intensity in the green detection window (500–570 nm, λ ex 488 nm), using confocal microscopy, while the emission intensity in the blue detection window (425–490 nm, λ ex 405 nm) remained relatively unchanged ( Figure 4 ) [ 220 ]. A more recent example has used nitrogen-doped GQDs to detect temperature in live HeLa cells by measuring the temperature-dependent fluorescence quenching as the cells are warmed from 25–45 °C [ 221 ].…”
Section: Imaging Agents Used For Fluorescence Microscopymentioning
confidence: 99%
“…In this regard, the design of reversible Advantages associated with the lifetime-based imaging can also be translated into the field of PL thermometry, which, in terms of steady-state PL approach, has been a staple for over a Carbonaceous materials, such as graphene NPs, are a biocompatible, water soluble alternative to SNCs. Although their quantum confinement-defined intrinsic PL lies in the ultraviolet to visible range, recent examples have shown that this can be shifted to the NIR through the modification of the synthesis process, [109][110][111] or judicious doping, 112 both yielding materials with PL properties tuned to the NIR-I or NIR-II. This way, reduced graphene oxide-derived NPs have been added…”
Section: Nanoscale Advances Accepted Manuscriptmentioning
confidence: 99%
“…to the existing library of NIR nanothermometers. 111 In addition, their strong absorption makes them ideal light-to-heat converters 110,112,113 for in vivo PTT and PL imaging when the absorption bands are tuned to the NIR. 110 Finally, the adequate dopant can also change graphene NPs sensitivity to the environment, which has been applied for pH sensing in the NIR.…”
Section: Nanoscale Advances Accepted Manuscriptmentioning
confidence: 99%